"Effectiveness of the Portfolio as learning stategy and resource focused on teaching english as a second language and as a subject for Hight School Students" - Acosta, Idalia; Martínez, Kevin; De Gracia, Edward; Vargas, Víctor (David, Panamá : UDELAS, 2013)
This research is about effectiveness of the use portfolio as a strategy and as a resource for teaching and learning english as second language. The principal objective is to promote the use od portfolio like tool and procedure to work in the classroom.
TABLE OF CONTENT TABLE OF CHART TABLE OF GRAPHIC INTRODUCTION CHAPTER I: BACKGROUND INFORMATION CHAPTER II: THEORETICAL FRAMEWORK 2.1. The grade of acceptance about portfolio 2.1.1. Definitions of portfolio 2.1.2. Classification of portfolio 2.1.2.1. Accordibg to its usage 2.1.2.2. According to the numbers of numbers 2.1.2.3. According to its form and structure 2.1.2.4. According its content 2.1.3. How to develop competences through portfolio 2.1.4. The portfolio and the approaches 2.2. Teacher and students roles developing the portfolio 2.2.1. The teacher's role 2.2.2. The student's role 2.2.3. Differencesbetween teacher portfolio and student portfolio 2.3. Benefits of the use of portfolio 2.3.1. Advantages as assessment tool 2.3.2. Advantage for students 2.3.3. Process to create an effective portfolio 2.4. Techniques in portfolio development 2.4.1. Techniques related to the treatment of information in the portfolio development 2.4.2. Evaluation techniques of portfolio 2.5. Portfolio assessment, a valid tool to evaluate students' achievements 2.5.1. What is portfolio assessment 2.6. Concept and purpose of using portfolios 2.7. E-portfolio 2.7.1. E-portfolio based learning 2.7.2. Supporting e-portfolio learners 2.8. Assessment of learning or assessment for learning CHAPTER III METHODOLOGYCAL FRAMEWORK CHAPTER IV DATA COLLECTION AND ANALYSIS OF THE RESULT CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY ANNEX
Incluye Table of content
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAL; LICENCIATURA EN DOCENCIA EN INGLÉS